Development of breast cancer mortality considering the implementation of mammography screening programs - a comparison of western European countries - Iwamoto, Yukio; Kaucher, Simone; Lorenz, Eva; Bärnighausen, Till; Winkler, Volker (BMC public health, 2019)
BACKGROUND: Triggered by the successive implementation of organized mammography screening programs (MSPs) throughout western European countries over the last decades, there is an ongoing debate questioning their effectiveness. Since it is difficult to assess the effect of MSPs on a population level, we rather aim to assess the impact of the implementation itself on breast cancer mortality rates utilizing an ecological study design. - METHODS: We analyzed age group-specific (50-59, 60-69 and 70-79 years) female breast cancer mortality rates in 14 western European countries between 1980 and 2017 using Joinpoint regression, interrupted time series (ITS) regression and multivariable Poisson regression. - RESULTS: The Joinpoint analysis demonstrated decreasing trends resulting in annual percentage changes ranging from - 1.5% to - 5.4% (50-59), - 0.2% to - 8.1% (60-69) and 0% to - 7.1% (70-79) depending on the country within 3 years after MSP implementation. The ITS analysis results in highly significant interaction terms (calendar year * binary MSP indicator) for all age groups. The multivariable regression using "calendar year", "year of MSP implementation" and "years with MSP" as independent variables yielded a significant yearly decrease for "years with MSP" ranging from 0.9 to 1.2%. - CONCLUSIONS: The results of this study suggest a positive association between the implementation of MSPs and the (accelerated) reduction of breast cancer mortality rates. Measuring and quantifying the isolated effect of MSPs on a population level will require additional studies using individual data.
Gesehen am 05.08.2019